Culture, connaissance et réduction des risques de catastrophe : liens critiques pour une transformation sociétale durable - Juergen Weichselgartner; John Norton; Guillaume Chantry; Emilie Brévière; Patrick Pigeon; Bernard Guézo (VertigO)
Disaster risk reduction policies and practices largely depend on the socio-cultural capacity and knowledge of people. Although culture and knowledge are critical issues for reducing disaster risks, both domains are seldom systematically addressed in-depth in disaster studies and policy programmes. We are convinced that tapping the rich portfolio of research on culture and knowledge systems will significantly improve the effectiveness of disaster mitigation. This article illustrates important aspects of culture and knowledge with regard to disaster risk reduction and outlines critical challenges. Subsequently, we present a conceptual approach for capturing different qualitative levels of understanding: facts, data, information, knowledge, and wisdom. Throughout the article, we use examples from Viet Nam to illustrate common cases of culture, economics, and popular practice prevailing over disaster risk reduction logic, as well as the barriers responsible for the fragmentation of knowledge. Shifting the research focus towards issues of culture and social knowledge would lead to a better apprehension and capture of the structural processes causing disaster vulnerability, as well as the social-cultural processes constructing our understanding of disaster risks.